The Exchange Rate Risk and Financial Sector Performance: Evidence from Nigeria - Funso, KOLAPO T.; Lawal, Naheem Abiola (Journal of Economics and Behavioral Studies, 2020)
This article looked at the connection between exchange rate risk and financial sector performance in Nigeria using time series data from 2008Q1 to 20017Q4. The study employed Autoregressive Conditional Heteroskedasticity (ARCH), and Granger Causality tests as estimation techniques. Financial intermediation index was used as the dependent variable while risk from exchange rate, risk from consumer price index and risk from interest rate were used as the independent variables. The findings from the study showed that exchange rate risk (EXR) coefficient value was -0.276230 with p-value of 0.0000, implying that EXR was negative and significant to influence FII. The risk from financial intermediation index reveals a coefficient value of -5.213590 and the p-value of 0.000 implying that when financial intermediation index increases, volatility or risk reduces which means that financial intermediation index was not a risky variable which was significant during the study period. However, the study concluded that the shock from exchange rate moves at a negative and significant direction to financial intermediation index of the economy. It is also concluded that exchange rate and financial intermediation index does not have uni or bi-directional relationships between each other. It is recommended that the Government and the Apex Bank of Nigeria are encouraged to increase the stabilization measurement for exchange rate to cushion its risk and by so doing; this could improve financial sector performance.